Evi5 is required for Xenopus limb and tail regeneration - Li Yang; Youwei Chen; Huahua Liu; Yu Liu; Feng Yuan; Qianyan Li; Gufa Lin (Frontiers in Cell and Developmental Biology, 2022)
Amphibians such as salamanders and the African clawed frog Xenopus are great models for regeneration studies because they can fully regenerate their lost organs. While axolotl can regenerate damaged organs throughout its lifetime, Xenopus has a limited regeneration capacity after metamorphosis. The ecotropic viral integrative factor 5 (Evi5) is of great interest because its expression is highly upregulated in the limb blastema of axolotls, but remains unchanged in the fibroblastema of post-metamorphic frogs. Yet, its role in regeneration-competent contexts in Xenopus has not been fully analyzed. Here we show that Evi5 is upregulated in Xenopus tadpoles after limb and tail amputation, as in axolotls. Down-regulation of Evi5 with morpholino antisense oligos (Mo) impairs limb development and limb blastema formation in Xenopus tadpoles. Mechanistically, we show that Evi5 knockdown significantly reduces proliferation of limb blastema cells and causes apoptosis, blocking the formation of regeneration blastema. RNA-sequencing analysis reveals that in addition to reduced PDGFα and TGFβ signaling pathways that are required for regeneration, evi5 Mo downregulates lysine demethylases Kdm6b and Kdm7a. And knockdown of Kdm6b or Kdm7a causes defective limb regeneration. Evi5 knockdown also impedes tail regeneration in Xenopus tadpoles and axolotl larvae, suggesting a conserved function of Evi5 in appendage regeneration. Thus, our results demonstrate that Evi5 plays a critical role in appendage regeneration in amphibians.